Multi-lateral strategic bargaining without stationarity - Carlos Alós-Ferrer; Klaus Ritzberger (Institute for Advanced Studies (IHS), 2017)
This paper establishes existence of subgame perfect equilibrium for a general class of sequential multi-lateral bargaining games. The only required hypothesis is that utility functions are continuous on the space of economic outcomes. In particular, no assumption on the space of feasible payoffs is needed. The result covers arbitrary and even time-varying bargaining protocols (acceptance rules), arbitrary specifications of patience or impatience (geometric, hyperbolic, or otherwise), externalities, multiple selves, and other-regarding preferences.
Keywords: 330; bargaining; equilibrium existence; infinite-horizon games; subgame perfection